Applicability of Maqasid Al-Shariah Towards Home Financing by Islamic Banks among University Staff in Malaysia - Hanudin Amin (Asian Academy of Management Journal, 2022)
Despite their significant growth, Islamic banks only consider about avoiding riba, gharar, and maysir at the expense of maqasid al-Shariah. The banks are somewhat converged with their conventional peers. Consumers believed that the banks imitate their peers pertinent to the pricing calculations and product lines. Without effective measure, consumers may discern Islamic banks undermine their maqasid objective and continued critics of mimicking their peers are prolonged. Against this backdrop, this study examines consumer preference using a proposed index known as the Maqasid Consumer Preference Index (MCPi). Drawing upon the MCPi, the present study examines consumer preference for six Islamic banks operated in Malaysia to which Islamic home financing products are presently made available. Our data were drawn from valid 450 usable questionnaires. The results obtained report that six Islamic banks relatively have a moderate index. Of these, Bank Islam Malaysia Berhad (BIMB) is ranked first, followed by Maybank Islamic, CIMB Islamic whilst Kuwait Finance House is ranked last. This work examines a new approach to measure consumer preference using the MCPi. Our contributions are confined to these particular factors – educating customer, establishing justice, and promoting welfare in the context of Islamic home financing in Malaysia. Future works may provide a different perspective on these interrogations by considering new dimensions to extend the findings. Despite this concern, the results obtained offer improved insights for bank managers to manage Islamic home financing products effectively.